Kinship Politics of Village Government in Lobulayan Sigordang Village West Angkola Districts South Tapanuli Regency - Rahma Yulianti Hutasuhut; Julia Ivanna (Randwick International of Social Science Journal, 2021)
This study aims to find out how kinship politics in village government in Lobulayan Sigordang Village, West Angkola District, South Tapanuli Regency includes the causal factors and patterns of the existence of kinship politics. This research is a case study research using a qualitative descriptive method. Data collection techniques in this study include observation, interviews, and documentation. In determining the research subjects used purposive sampling technique, so in this study the research subjects were the Head of Lobulayan Sigordang Village, Secretary of Lobulayan Sigordang Village, Head of Government Section, Head of Community Section, Head of Financial Affairs, and Head of Planning Affairs. The research data were obtained through observations, interviews, and documentation, then processed and analyzed by first reducing the data then displaying the data in tabular form and the last narrative description drawing conclusions on the findings of the research data. Based on the research that has been done, there is kinship politics in the village government in Lobulayan Sigordang village, the manifestation of kinship politics is seen from the election of village officials who occupy village officials positions that are not based on their abilities or not through a predetermined procedure, but rather based on on consideration of good kinship because of blood ties, marital ties, and clans. The factors behind kinship politics in Lobulayan Sigordang village are: low level of education, assessing that kinship politics is not a wrong thing, and feelings of not being betrayed by family or relatives in running the village government.